PEMANFAATAN ABU VULKANIK PADA PAVING BLOCK SEBAGAI PENGEMBANGAN BAHAN AJAR MATA KULIAH ILMU BAHAN BANGUNAN - Sari, Vivit Rulita; Sumarni, Sri; Sri, Ernawati (Pendidikan Teknik Bangunan, 2015)
Volcanic ash is a natural substance produced from eruption. It is used as material for paving block functioning as a partial replacement of fine aggregate. The results are applied to develop the teaching materials on building materials science subject.The purpose of this study is to determine the effect of volcanic ash on the compressive strength and permeability of paving blocks. This study applied an experimental method in laboratory by testing the samples. The samples used in this research are paving blocks with size of 6,5 x 10 x 20 cm with a total sample of 45 pieces. The variations are from 0%, 5%, 10%, 20% and 25% ash replacing fine aggregate. Each group sample contains 9 pieces. The calibration is applying the compressive strength and permeability testing.The replacement of volcanic ash as a partial replacement of fine aggregate in the manufacture of paving blocks indicates a positive impact. Optimal values achieved for compressive strength is 30,8 MPa of 10,4% variation replacement, whereas, the optimum permeability best value achieved is at variation of 16,6875% in the permeability of 8,416%.Keywords: paving block, volcanic ash, compressive strength and permeability